Soil aggregate structure, stability, and stoichiometric characteristics in a smelter-impacted soil under phytoremediation - Xu, Lei; Xing, Xiangyu; Bai, Jingfeng; Li, Ding (Frontiers in Environmental Science, 2022)
Smelter-impacted soils often result in soil degradation and the destruction of the soil structure. Although soil aggregate typically plays a crucial role in soil structure, the influence of phytoremediation on soil aggregate structure stability and stoichiometric characteristics remains unclear. To study the influence of phytoremediation on soil aggregate structure, stability and stoichiometric characteristics, a 3-year in situ experiment was conducted. After hydroxyapatite was applied, Elsholtzia splendens, Sedum plumbizincicola, and Pennisetum sp. were planted in a smelter-impacted soil. After 3 years, the soil aggregate structure, stability, and stoichiometric of chemical elements were analyzed. The results showed that the three phytoremediation treatments increased the content of >0.25 mm mechanically-stable (DR0.25) and water-stable (WR0.25) aggregates by 6.6%–10.4% and 13.3%–17.5%, respectively. Aggregate mean weight diameter (MWD), geometric mean diameter, and aggregate stability rate (AR, %) were significantly increased, and the soil mechanically stable aggregate fractal dimension (D) was significantly reduced after the 3-year remediation. Soil total nitrogen and phosphorus in aggregates with different particle sizes were significantly increased by 11.4%–46.4% and 107%–236% after different plant treatments. For the stoichiometric characteristics of the aggregates, the combined remediation only significantly reduced the value of N:P and C:P in different particle size aggregates and had no significant effect on the C:N in all particle size aggregates. Meanwhile, the combined remediation of hydroxyapatite and Elsholtzia splendens, Sedum plumbizincicola, and Pennisetum sp. in heavy metal heavily contaminated soil could reduce the availability of Cu and Cd by 54.1%–72.3% and 20.3%–47.2% during the 3 years, respectively. In summary, this combined remediation method can be used for the remediation of farmland that is contaminated by heavy metals.